2018
DOI: 10.1521/pedi_2017_31_296
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and Deviant Workplace Behavior: A Comparison of Two Psychopathy Models

Abstract: Although psychopathy is an interpersonally harmful construct, few studies have compared different psycho athy models in predicting different types of workplace deviance. We examined how the Triarchic Psychopathy Model (TRI-PM) and the Self-Report Psychopathy-Short Form (SRP-SF) predicted deviant workplace behaviors in two forms: sexual harassment and deviant work behaviors. Using structural equations modeling, the latent factor of psychopathy was predictive for both types of deviant workplace behavior. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…So far, reports shedding light on the measurement model of the TriPM, such as using factor analysis, are sparse. The studies that are available do not provide clear evidence for the three dimensions in the original measurement model, based on standard criteria of good model fit (8,(49)(50)(51). Furthermore, the items of the TriPM display varying associations to the hypothesized factors, with several items loading weakly to the intended factor, as well as cross-loading to the other factors (8,50).…”
Section: Discussionmentioning
confidence: 99%
“…So far, reports shedding light on the measurement model of the TriPM, such as using factor analysis, are sparse. The studies that are available do not provide clear evidence for the three dimensions in the original measurement model, based on standard criteria of good model fit (8,(49)(50)(51). Furthermore, the items of the TriPM display varying associations to the hypothesized factors, with several items loading weakly to the intended factor, as well as cross-loading to the other factors (8,50).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies and theoretical discussions claim that injunctive norms and descriptive norms that perceived are two dimensions of perceived group norms (Carre et al, 2017;Golparvar, 2015;Harisur et al, 2018). Injunctive norms explains the type of behaviors that many members of the group approve or reject (Khattak, Khan, Fatima, Zul, & Shah, 2018;Tuna et al, 2016;Wang, Chen, & Li, 2018).…”
Section: Perceived Group Normsmentioning
confidence: 99%
“…Deviant workplace behavior is a prevailing and expensive occurrence for organizations (Ahad, Mustafa, Mohamad, Abdullah, & Nordin, 2021). Different studies concluded that deviant workplace behavior not only cost an extensive amount of money annually to the organizations, also they have psychological and negative concerns for employees as well (Carre, Mueller, Schleicher, & Jones, 2017;Chang, Chou, & Han, 2018). For instance, Mohamed, Zeinhom, Higazee, & Goda, (2018) reported that employee theft was attributed to about 45% of the United States retailers' inventory shortage in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to psychopathy's multidimensionality, psychopathy subdimensions often bear distinct relations with various forms of sexual aggression (Carre, Mueller, Schleicher, & Jones, 2018;Marcus & Norris, 2014). Triarchic dimensions are associated with a broad swath of traits and behaviors ostensibly adjacent to ISOP, including workplace sexual harassment 1 (Carre et al,1 Sexual harassment bears superficial similarities to ISOP behaviors.…”
Section: Extending the Nomological Network Of Sexual Objectification mentioning
confidence: 99%
“…Impulsigenic traits (Sharma, Markon, & Clark, 2014), including disinhibition and sensation seeking, are involved in myriad of sexual harassment, such as covert evaluation of others' sexual body parts. Sexual harassment entails behaviors that are not encompassed by ISOP, such as telling inappropriate sexual jokes, espousing gendered stereotypes, attempts at sexual coercion, and a willingness to capitalize on workplace power dynamics (Carre et al, 2018;Pryor, 1987). externalizing behaviors that manifest in maladaptive sexual behavior (e.g., Dir, Coskunpinar, & Cyders, 2014).…”
Section: Extending the Nomological Network Of Sexual Objectification mentioning
confidence: 99%